Carotid Endarterectomy in a Patient with Posterior Cerebral Artery Infarction: Influence of Fetal Type PCA on Atypical Clinical Course - Mehmet Kolukısa; Azize Esra Gürsoy; Gülşen Kocaman; Hümeyra Dürüyen; Hüseyin Toprak; Talip Asil (Case Reports in Neurological Medicine)
Fetal type PCA may positively affect clinical outcome in patients with ischemic stroke such as protection of a reserve blood flow capacity as well as negative effect on clinical outcome such as certain atypical pathological manifestations. We presented a patient with a posterior cerebral artery territory infarction due to an unexpected etiology as stenosis of internal carotid artery (ICA) with existence of fetal type PCA.